The impact of interpersonal relationships on rural doctors’ clinical courage - Lucie Walters; Ian Couper; Ruth Stewart; David Campbell; Jill Konkin (James Cook University, 2021)
Introduction: Clinical courage occurs when rural doctors push themselves to the limits of their scope of practice to provide the medical care needed by patients in their community. This mental strength to venture, persevere and act out of concern for one's patient, despite a lack of formally recognised expertise, becomes necessary for doctors who work in relative professional isolation. Previous research by the authors suggested that the clinical courage of rural doctors relies on the relationships around them. This article explores in more depth how relationships with others can impact on clinical courage. Methods: At an international rural medicine conference in 2017, doctors who practised rural/remote medicine were invited to participate in the study. Twenty-seven semistructured interviews were conducted exploring experiences of clinical courage. Initial analysis of the material, using a hermeneutic phenomenological frame, sought to understand the meaning of clinical courage. In the original analysis, an emic question arose: 'How do interpersonal relationships impact on clinical courage'. The material was re-analysed to explore this question, using Wenger's community of practice as a theoretical framework. Results: This study found that clinical courage was affected by the relationships rural doctors had with their communities and patients, with each other, with the local members of their healthcare team and with other colleagues and health leaders outside their immediate community of practice. Conclusion: As a collective, rural doctors can learn, use and strengthen clinical courage and support its development in new members of the discipline. Relationships with rural communities, rural patients and urban colleagues can support the clinical courage of rural doctors. When detractors challenge the value of clinical courage, it requires individual rural doctors and their community of practice to champion rural doctors' way of working.